Foraging ecology of the greater adjutant stork, Leptoptilos dubius in certain wetlands and a garbage dump in Assam, India - Devi Barman, Purnima; Sharma, D. K. (Academia Journal of Biology, 2025)
The Greater Adjutant Stork (Leptoptilos dubius), a Near Threatened species, was studied from 2012 to 2017 across wetlands, paddy fields, and a garbage dump in Assam’s Brahmaputra Valley. Observations during breeding and non-breeding seasons assessed habitat-specific foraging behavior and adaptability. Foraging activity peaked in wetlands during the breeding season, especially in December and February. Foraging rates ranged from 0.7–2.0 minutes in wetlands and 1.0–4.0 minutes at the garbage dump. Wetlands with shallow water (1–10 cm) showed the highest foraging success (85.1%), decreasing with depth; paddy fields had lower success (70.6%). Prey handling time increased with size, particularly for prey ≥ 30 cm (60–140 seconds), and was most efficient at 1–30 cm depth. Handling time correlated positively with water depth (r = 0.860) and number of footsteps (r = 0.478). Storks used visual, tactile, and combined foraging techniques depending on habitat. In captivity, Cyprinids were preferred; Monopterus cuchia showed high profitability despite longer handling. Regurgitated food from nests confirmed a diet dominated by Channa and Cyprinids. Morphometric traits like long bills and legs support efficient foraging in shallow wetlands. These findings highlight the stork’s behavioral flexibility and emphasize wetland conservation as vital to sustaining foraging habitats and guiding conservation efforts.